Fiqih sosial dan kurikulum pendidikan Islam: Menjawab tantangan keberagaman di era globalisasi - Fariati, Betti; Chanifudin, Chanifudin (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2025)
This study discusses the integration of social fiqh in the Islamic education curriculum as a response to the challenges of diversity in the era of globalization. The social fiqh approach that emphasizes the values ​​of welfare and social justice is relevant in creating inclusive education that respects cultural, religious, and global value diversity. This study uses a library research method with data collection techniques through documentation and data analysis techniques using an interpretive approach. The results of the study indicate that social fiqh can be applied in the curriculum through revision of learning themes that include diversity values, development of teacher competencies for inclusive teaching, and the use of digital technology as a learning medium. The conclusion of the study confirms that social fiqh is a relevant philosophical foundation for building Islamic education that is responsive to diversity as well as adaptive to global dynamics.